Fly ash-based geopolymer carbon sequestration adsorption material and preparation method thereof
By introducing 13X zeolite into fly ash ground polymer and performing hydrothermal conversion, the pore structure and specific surface area of the material are improved, and the problem of low efficiency of existing fly ash mineralized CO2 storage technology is solved, and the adsorption capacity of carbon dioxide is significantly improved.
Patent Information
- Application Number
- CN202510353139.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-25
AI Technical Summary
The existing fly ash mineralized storage and storage CO2 technology has problems such as low mineralization efficiency, unstable reaction products and low strength, making it difficult to effectively improve the adsorption capacity of carbon dioxide.
By adding 13X zeolite to fly ash landpolymer and performing hydrothermal conversion under alkaline conditions, the micropore, mesoporous pore structure and specific surface area of the material are improved, thereby significantly improving its carbon dioxide adsorption capacity.
The microporous and mesoporous porosity and specific surface area of fly ash-based modified polymer were significantly improved, and its adsorption capacity to carbon dioxide was enhanced. The adsorption amount reached 70.6 cm3/g, which was nearly 28 times higher than that of unmodified materials.
Smart Images

Figure CN119869447A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of engineering materials and discloses a fly ash-based polymer carbon fixation adsorption material and a preparation method thereof. Background Art
[0002] Mining activities will form huge underground spaces in abandoned mines. Disposing solid waste materials that can absorb CO2 in abandoned underground spaces will help to break the technical bottleneck of the coordinated disposal of carbon waste in underground spaces of closed mines, realize the technical upgrade of the underground carbon storage industry from passive carbon sealing to active carbon sealing, and transform these abandoned spaces into large-scale underground spaces for coordinated storage of carbon waste. The Guiding Opinions on the Comprehensive Utilization of Bulk Solid Waste point out that the efficiency of the utilization of bulk solid waste should be improved. At present, the main method of co-disposal of carbon waste in underground spaces is to react solid waste with CO2 to generate mineralized (carbonate) filling materials. The mineralized filling materials formed by this method have defects such as low mineralization efficiency (depending on the high temperature environment), unstable reaction products (partial products at high temperature are easy to decompose), and low strength (low bonding strength between particles). Therefore, it is urgent to break through the constraints of fly ash mineralization and storage of CO2.
[0003] Geopolymer, as a porous material, has the potential to adsorb CO2. At present, some scholars have added rice husk ash (microporous material) into geopolymer. Although it can increase the micropores (<2 nm) in the system and improve the CO2 adsorption capacity to a certain extent, it only enhances the CO2 adsorption capacity by adding microporous materials, and does not give full play to the adsorption potential brought by the pores of different scales of geopolymer. Therefore, the present invention first increases the proportion of micropores in geopolymer by introducing microporous materials with high adsorption performance, and then further converts the pores in geopolymer into micropores (<2 nm) and mesopores (2-50 nm) by hydrothermal conversion of geopolymer, comprehensively improves the proportion of micropores and mesopores in geopolymer, and significantly improves the adsorption capacity of modified carbon-fixing geopolymer for CO2. Summary of the invention
[0004] In view of the high reactivity of aluminosilicate in fly ash, the excellent performance of 13X zeolite in adsorbing CO2, and the significant effect of phase change transformation of conventional geopolymers to zeolites in enhancing the specific surface area of the material, the present application provides a fly ash-based polymer carbon fixation adsorption material and a preparation method thereof. By adding 13X zeolite to fly ash geopolymer and then conducting hydrothermal transformation under alkaline conditions to comprehensively improve the micropore and mesopore pore structure of the material and increase the specific surface area of the material, its carbon dioxide adsorption capacity will be significantly improved.
[0005] Among them, fly ash is rich in highly reactive silicon oxide and aluminum oxide. After reacting with alkaline solution, a series of chemical reactions such as depolymerization and condensation will occur to synthesize a stable three-dimensional grid material with a large number of pores, which can provide a large number of adsorption sites for the storage of carbon dioxide.
[0006] In addition, the proportion of micropores in conventional geopolymers is small, and micropores are an important factor affecting the specific surface area and adsorption performance of geopolymers. The effective pore size of 13X zeolite is about 1 nm, which can effectively adsorb CO2 gas molecules with a diameter of about 0.33 nm. Due to its large specific surface area and high metal cation content, it can interact with CO2 during the adsorption process, thereby effectively capturing CO2. If 13X zeolite can be introduced into geopolymers, the proportion of micropores and CO2 adsorption potential of geopolymers will be significantly improved. In addition, the non-crystalline three-dimensional gel network structure of geopolymers is thermodynamically unstable, which means that they will very slowly transform into zeolite crystal phase at room temperature and pressure. Transforming into zeolite crystal phase will significantly increase the proportion of micropores and mesopores, specific surface area and CO2 adsorption potential of the material. This process may take a long time. Accelerating this phase change process in a specific environment and improving the efficiency and integrity of the phase change will bring hope for further enhancing CO2 adsorption performance. Therefore, the introduction of 13X zeolite to enhance the micropore ratio of geopolymer materials and the phase transformation of geopolymer to zeolite under specific environment to enhance its micropore and mesopore ratio will comprehensively improve the micropores and mesopores that affect the CO2 adsorption potential of geopolymers and synthesize new solid waste-based high-efficiency carbon fixation materials. It has broad prospects and significance for promoting the realization of carbon sequestration, solid waste disposal, and transforming abandoned mine space into carbon waste disposal space.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] The first technical purpose of the present invention is to provide a fly ash-based polymer carbon fixation adsorption material, which is mainly prepared from the following substances:
[0009] 100 parts of fly ash, 55-70 parts of water, 10-34 parts of 13X zeolite, and 15-38 parts of alkali activator.
[0010] Optionally, the fly ash-based polymer carbon fixation adsorption material has a solid-liquid mass ratio of 0.55-0.7, a silicon-aluminum molar ratio of 1.7-2.0, and a constant curing temperature of 80°C.
[0011] Optionally, the alkaline activator is a mixed powder of sodium hydroxide and sodium silicate, and the alkaline activator comprises 12 to 27 parts of sodium silicate and 3 to 11 parts of sodium hydroxide in parts by weight;
[0012] Moreover, the modulus of the alkaline activator is 0.8-1.1, which is the molar ratio of SiO2 to Na2O; the sodium hydroxide is analytically pure powder; and the sodium silicate is analytically pure powder with a modulus of 2.8.
[0013] Optionally, the 13X zeolite is a white powder with a pore size of about 1 nm, and CO2 molecules can be adsorbed in the pores; the particle size is 2 μm~4 μm, and the bulk density is ≥0.33 g / mL, so as to be better dispersed in the geopolymer slurry.
[0014] The second technical purpose of the present invention is to provide a method for preparing the fly ash-based polymer carbon fixation adsorption material, which specifically comprises the following steps:
[0015] S1: Dissolve sodium hydroxide in water at room temperature. After it is completely dissolved and restored to room temperature, heat it in a water bath to 50°C and maintain the temperature. Then, add sodium silicate in batches in a ratio of 1 to 2 parts while stirring until the sodium silicate is completely dissolved, thereby preparing an alkaline activator solution.
[0016] S2: After the alkaline activator solution described in S1 is cooled to room temperature, fly ash is gradually added thereto while being stirred with a glass rod to form a geopolymer slurry. The slurry is then stirred at a speed of 400 r / min on a disperser for 4 to 6 minutes to ensure uniform mixing.
[0017] S3: The geopolymer slurry obtained in step S2 is taken out from the disperser, and then 13X zeolite is added in batches, and the weight parts added in batches are 3.4 parts. After each addition of 13X zeolite, it is necessary to stir again on the disperser at a speed of 400 r / min for 1 to 2 minutes to ensure that the 13X zeolite and the slurry are fully mixed, so as to prepare a fly ash-13X zeolite composite geopolymer slurry.
[0018] S4: Pour the fly ash-13X zeolite composite geopolymer slurry described in S3 into a plastic mold, cure it in a constant temperature box at 80° C. for 24 h, then take it out and demould it.
[0019] S5: Place the demoulding geopolymer sample described in S4 into a polytetrafluoroethylene-lined reactor, add 2 mol / L sodium hydroxide solution into the reactor, and place the reactor in a 100°C constant temperature box for hydrothermal reaction for 48 hours; take out the geopolymer sample from the reactor, and wash it repeatedly with deionized water until the pH of the washed liquid is close to 8; place the sample in a constant temperature box and dry it at 60°C. After drying, a fly ash-based modified geopolymer carbon-fixing material is obtained.
[0020] It should be noted that the material of the present invention is modified by adding 13X zeolite of a specific particle size, and its carbon fixation adsorption performance is significantly improved by an in-situ hydrothermal conversion process. The fly ash-based polymer material and preparation method disclosed in the present invention are simple and easy to implement in industrial production. They can overcome the shortcomings of direct reaction of solid waste with CO2 to generate mineralized (carbonate) filling materials, low mineralization efficiency and unstable reaction products, and make full use of the inherent characteristics of geopolymer materials. By introducing 13X zeolite into fly ash-based polymers, the micropore porosity of the material is improved; the mesoporous porosity and microporous porosity are improved by in-situ hydrothermal conversion, and the micropores and mesopores of the material are comprehensively improved, giving the material extremely high porosity and specific surface area, and significantly enhancing its CO2 adsorption performance. The geopolymer carbon fixation adsorption material of the present invention has a wide range of application prospects, and provides a new method for collaboratively solving carbon sequestration, solid waste disposal, and waste underground space reuse, with important environmental, social and economic benefits.
[0021] It can be seen from the above technical solution that, compared with the prior art, the present invention provides a fly ash-based polymer carbon fixation adsorption material and a preparation method thereof, which has the following excellent effects:
[0022] The present invention introduces 13X zeolite into geopolymer, selects the optimal formula of geopolymer with the most micropores and the largest specific surface area, and then hydrothermally converts the 13 zeolite-modified geopolymer with the largest specific surface area. The 13X zeolite-modified geopolymer introduces nano-scale micropores into the fly ash-based polymer by introducing 13X zeolite, and improves the micropore and mesopore structure of the geopolymer itself by hydrothermal conversion of the geopolymer material, thereby significantly increasing the micropore and mesopore porosity of the carbon-fixing geopolymer and the specific surface area that affects the adsorption performance. The specific surface area reaches 359.98 m 2 / g, which is nearly 30 times higher than before improvement, significantly enhancing the carbon dioxide adsorption capacity of the material. Under the working conditions of 40 ℃ and 5 MPa, the carbon dioxide adsorption capacity of the geopolymer after the introduction of 13X zeolite and hydrothermal conversion reached 70.6 cm 3 / g, and the CO2 adsorption capacity of the optimal geopolymer without hydrothermal conversion after the introduction of 13X zeolite was 36.7 cm 3 / g, without the introduction of 13X zeolite or hydrothermal conversion, the carbon dioxide adsorption capacity of the geopolymer is 2.5 cm 3 / g. Therefore, the introduction of 13X zeolite into geopolymer and hydrothermal conversion increased the storage capacity by nearly 28 times compared with the introduction of 13X zeolite and no hydrothermal conversion, and increased it by 1.9 times compared with the introduction of 13X zeolite without hydrothermal conversion. In addition, according to the actual gas state equation, the storage capacity of net space carbon dioxide is about 107.6 kg / m 3 The geopolymer filling of the present invention can achieve a carbon dioxide storage capacity of 137.3 kg / m 3, an increase of nearly 28% year-on-year, and solid waste fly ash was also disposed of. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to clearly illustrate the technical solutions in the examples of the present invention, the following briefly introduces the drawings required in the embodiments or prior art descriptions. It should be noted that the drawings in the descriptions are only embodiments of the present invention, and their function is to enable those skilled in the art or ordinary technicians to obtain other drawings based on the provided drawings without creative work.
[0024] Figure 1 It is a schematic diagram of the method for preparing the fly ash-based polymer carbon fixation adsorption material disclosed in the present invention.
[0025] Figure 2 This is the XRD spectrum of geopolymer.
[0026] Figure 3 This is the low-temperature liquid nitrogen adsorption diagram of geopolymer.
[0027] Figure 4 This is the pore size distribution of geopolymer (2-150 nm).
[0028] Figure 5 Field emission electron microscopy (a is raw fly ash, b is geopolymer without any modification, c and d are geopolymer with added 13X zeolite, e and f are geopolymer modified by hydrothermal process).
[0029] Figure 6 It is the Fourier infrared spectrum.
[0030] Figure 7 This is the isotherm adsorption diagram of GEO-0.
[0031] Figure 8 This is the GEO-6 adsorption isotherm.
[0032] Fig. 9 This is the isotherm adsorption diagram of GEO-6HC. DETAILED DESCRIPTION
[0033] The technical solution disclosed in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention and the drawings of the specification. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The embodiment of the invention discloses a method for preparing a fly ash-based polymer carbon fixation adsorption material.
[0035] In order to better understand the present invention, the present invention is further specifically described below through the following specific embodiments, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.
[0036] In order to simplify the number of experiments, the implementation method uses an orthogonal experiment to design four factors and four levels, a total of 16 groups of experiments as examples (GEO-1~GEO-16) and comparative examples (GEO-0), to find the optimal formula with high specific surface area and porosity, and then conduct a hydrothermal conversion experiment. The experimental scheme is shown in Table 1. According to the data in Table 1, even if fly ash from different sources (different silicon oxide and aluminum oxide contents) is used, samples with the same chemical composition can be prepared according to the parameters in the table.
[0037] Table 1 Experimental group settings
[0038]
[0039] It should be noted that the micropore specific surface area measured by the carbon dioxide adsorption test showed that the GEO-6 group had the highest specific surface area. Therefore, the silicon-aluminum ratio, solid-liquid mass ratio, and alkaline activator modulus of the control group GEO-0 were consistent with those of the GEO-6 group, and the GEO-0 group did not add 13X zeolite.
[0040] In view of the fact that the GEO-6 group has the highest specific surface area, the geopolymer is prepared with the chemical components of the GEO-6 group, and the generated geopolymer is hydrothermally converted to finally form the GEO-6HC hydrothermal conversion group.
[0041] Since the production processes are similar, the production processes of some samples are listed below.
[0042] Comparative example (GEO-0):
[0043] (1) The fly ash geopolymer prepared by GEO-0 has the following physical properties: solid-liquid mass ratio is 0.6; silicon-aluminum molar ratio is 1.8.
[0044] (2) The fly ash geopolymer prepared by GEO-0 includes the following components in terms of mass fraction: 100 parts of fly ash, 70 parts of water, 0 parts of 13X zeolite, and 15 parts of an alkali activator, including 12 parts of sodium silicate and 3 parts of sodium hydroxide.
[0045] (3) The alkaline activator used in the comparative example is a mixed powder of sodium hydroxide and sodium silicate, wherein the sodium hydroxide is an analytically pure powder, and the sodium silicate is an analytically pure powder, and the modulus thereof is 2.8. The modulus of the mixed sodium hydroxide and sodium silicate is 0.8.
[0046] (4) Dissolve sodium hydroxide in water at room temperature. After it is completely dissolved and returns to room temperature, heat it in a water bath to 50°C and maintain the temperature. Then, add sodium silicate in batches in a ratio of 1 to 2 parts while stirring until the sodium silicate is completely dissolved, thereby preparing an alkaline activator solution.
[0047] (5) After the alkaline activator solution described in (4) is cooled to room temperature, fly ash is gradually added thereto while stirring with a glass rod to prepare a geopolymer slurry. The slurry is then stirred at 400 r / min on a disperser for 6 minutes to ensure uniform mixing.
[0048] (6) Pour the geopolymer slurry described in (5) into a plastic mold, cure it in a thermostatic oven at 80° C. for 24 h, then take it out and demould it.
[0049] (7) After preparation, the samples were characterized by field emission electron microscopy (FSEM) and energy dispersive spectrometer (EDS), X-ray diffraction analysis (XRD), liquid nitrogen testing of specific surface area and pore distribution (2-500 nm), and carbon dioxide testing of micropores (≤2 nm).
[0050] Example GEO-6
[0051] (1) Example GEO-6 The fly ash geopolymer prepared has the following physical properties: solid-liquid mass ratio is 0.6; silicon-aluminum molar ratio is 1.8.
[0052] (2) Example GEO-6 The fly ash geopolymer prepared comprises the following components in terms of mass fraction: 100 parts of fly ash, 60 parts of water, 34 parts of 13X zeolite, and 24 parts of an alkali activator, including 17 parts of sodium silicate and 7 parts of sodium hydroxide.
[0053] (3) The alkaline activator used in Example GEO-6 is a mixed powder of sodium hydroxide and sodium silicate, wherein the sodium hydroxide is an analytically pure powder, and the sodium silicate is an analytically pure powder, and the modulus thereof is 2.8. The modulus of the mixed sodium hydroxide and sodium silicate is 0.8.
[0054] (4) The 13X zeolite used in Example GEO-6 is a white powder with a particle size of 2 μm to 4 μm and a bulk density of ≥0.33 g / mL.
[0055] (5) Dissolve sodium hydroxide in water at room temperature. After it is completely dissolved and returns to room temperature, heat it in a water bath to 50°C and maintain this temperature. Then, add sodium silicate in batches in a ratio of 1 to 2 parts while stirring until the sodium silicate is completely dissolved, thereby preparing an alkaline activator solution.
[0056] (6) After the alkaline activator solution described in (5) is cooled to room temperature, fly ash is gradually added thereto while stirring with a glass rod to prepare a geopolymer slurry. The slurry is then stirred at 400 r / min on a disperser for 6 minutes to ensure uniform mixing.
[0057] (7) The geopolymer slurry obtained in (6) was taken out from the disperser, and then 13X zeolite was added in batches, 3.4 parts each time, and the total amount added was 34 parts; after each addition of 13X zeolite, it was necessary to stir it again at a speed of 400 r / min on the disperser for 2 minutes to ensure that the 13X zeolite and the slurry were fully mixed, so as to prepare the fly ash-13X zeolite composite geopolymer slurry.
[0058] (8) Pour the fly ash-13X zeolite composite geopolymer slurry described in S3 in (7) into a plastic mold, cure it in a thermostat at 80° C. for 24 hours, then take it out and demould it.
[0059] (9) After preparation, the samples were characterized by field emission electron microscopy (FSEM) and energy spectrum measurement, X-ray diffraction analysis (XRD), liquid nitrogen testing of specific surface area and pore distribution (2-500 nm), and carbon dioxide micropore (≤2 nm) pore distribution.
[0060] Example GEO-6HC hydrothermal conversion group
[0061] (1) Example The fly ash geopolymer prepared by GEO-6HC under the combined influence of multiple foaming agents has the following physical properties: solid-liquid mass ratio is 0.6; silicon-aluminum molar ratio is 1.8.
[0062] (2) Example GEO-6HC The fly ash geopolymer prepared comprises the following components in terms of mass fraction: 100 parts of fly ash, 60 parts of water, 34 parts of 13X zeolite, and 24 parts of an alkali activator, including 17 parts of sodium silicate and 7 parts of sodium hydroxide.
[0063] (3) Example GEO-6HC The alkaline activator used is a mixed powder of sodium hydroxide and sodium silicate, wherein the sodium hydroxide is an analytically pure powder, and the sodium silicate is an analytically pure powder, and the modulus thereof is 2.8. The modulus of the mixed sodium hydroxide and sodium silicate is 0.8.
[0064] (4) Example The 13X zeolite used in GEO-6HC is a white powder with a particle size of 2 μm to 4 μm and a bulk density of ≥0.33 g / mL.
[0065] (5) Dissolve sodium hydroxide in water at room temperature. After it is completely dissolved and returns to room temperature, heat it in a water bath to 50°C and maintain this temperature. Then, add sodium silicate in batches in a ratio of 1 to 2 parts while stirring until the sodium silicate is completely dissolved, thereby preparing an alkaline activator solution.
[0066] (6) After the alkaline activator solution described in (5) is cooled to room temperature, fly ash is gradually added thereto while stirring with a glass rod to prepare a geopolymer slurry. The slurry is then stirred at 400 r / min on a disperser for 6 minutes to ensure uniform mixing.
[0067] (7) The geopolymer slurry obtained in (6) was taken out from the disperser, and then 13X zeolite was added in batches, 3.4 parts each time, and the total amount added was 34 parts; after each addition of 13X zeolite, it was necessary to stir it again at a speed of 400 r / min on the disperser for 2 minutes to ensure that the 13X zeolite and the slurry were fully mixed, so as to prepare the fly ash-13X zeolite composite geopolymer slurry.
[0068] (8) Pour the fly ash-13X zeolite composite geopolymer slurry described in (7) into a plastic mold, cure it in a thermostatic oven at 80°C for 24 h, then take it out and demould it.
[0069] (9) The demolded geopolymer sample described in (8) was placed in a polytetrafluoroethylene-lined reactor, 2 mol / L sodium hydroxide solution was added to the reactor, and the reactor was placed in a constant temperature box at 100 °C for 48 h; the geopolymer sample was taken out of the reactor and repeatedly washed with deionized water until the pH of the washed liquid was close to 8; the sample was placed in a constant temperature box at 60 °C for drying, and after drying, the fly ash-based modified geopolymer carbon-fixing material was obtained.
[0070] (10) After preparation, the samples were characterized by field emission electron microscopy (FSEM) and energy spectrum measurement, X-ray diffraction analysis (XRD), liquid nitrogen testing of specific surface area and pore distribution (2-500 nm), and carbon dioxide testing of micropores (≤2 nm).
[0071] Performance Testing
[0072] The samples were subjected to X-ray diffraction analysis (XRD), field emission electron microscopy analysis (FSEM), specific surface area and pore analysis, and the specific surface area, porosity and porosity of different pore sizes were statistically analyzed for range analysis.
[0073] 1) XRD diffraction analysis such as Figure 2 As shown:
[0074] X-ray diffraction analysis was used to analyze the phases of the geopolymer samples. Curve 1 is the spectrum of fly ash, curve 2 is the spectrum of fly ash-based geopolymer (GEO-0), curve 3 is the spectrum of fly ash-based geopolymer (GEO-6) with the addition of 13X zeolite, and curve 4 is the spectrum of fly ash-based geopolymer (GEO-6HC) with the addition of 13X zeolite and hydrothermal conversion.
[0075] It can be seen from curve 1 that fly ash contains components such as quartz and mullite, and there is a bulge between 10° and 30°, which represents the amorphous glass of fly ash.
[0076] As can be seen from curve 2, after a series of reactions during the preparation of geopolymer, the bulge from 10° to 30° shifted to between 20° and 40°, showing a diffuse, bun-shaped peak, proving that the glass in the fly ash dissolved and formed a new amorphous gel material. After preparation, quartz and mullite phases still exist in GEO-0, indicating that quartz and mullite did not participate in the reaction during the polymerization of geopolymer.
[0077] It can be seen from curve 3 that GEO-6 has added 13X zeolite, and the crystal phase of X-type zeolite is also detected in the spectrum. The peak intensity of quartz and mullite in the spectrum is weaker than that in curve 2, which proves that the added 13X zeolite and geopolymer can coexist and be evenly mixed.
[0078] It can be seen from curve 4 that compared with the sample without hydrothermal conversion (curve 3), a large number of new zeolite crystal phases are formed and some existing zeolite crystal phases are enhanced, proving that the pore structure of the geopolymer is optimized, providing more adsorption sites for the adsorption of CO2. In fact, under such alkaline and high temperature conditions, the alkaline environment provides favorable conditions for the nucleation and growth of zeolite crystals. The non-crystalline three-dimensional gel dissolves in the alkaline environment, rearranges and reorganizes to form nano-ordered zeolite crystals. The high temperature environment will accelerate the phase change reaction process. The above phase change process will increase the porosity and specific surface area of the material and enhance the CO2 adsorption performance.
[0079] 2) Specific surface area and pore analysis such as Figure 3 As shown:
[0080] When the relative pressure (P / P0) is low, the adsorption capacity of GEO-6 quickly reaches 30 cm 3 / g, and the adsorption capacity of GEO-6HC reached 50 cm 3 / g. This part represents the microporous part of the material. The adsorption amount of both increased rapidly, which proved that the added 13X zeolite did not react and existed evenly in the carbon-fixing material. The initial adsorption amount of GEO-6HC was higher than that of GEO-6. It was analyzed that under the action of hydrothermal, additional microporous pores were further formed inside the material.
[0081] When the relative pressure P / P0=0.5, the corresponding pore size is about 4 nm, and the adsorption amount at this time is approximately equal to the filling volume of the micropores. Hysteresis loops appeared in all three samples. GEO-6 showed a smaller hysteresis loop at a relative pressure of about 0.8. According to the latest IUPAC classification, it is similar to the H4 type hysteresis loop. This type of hysteresis loop usually appears on adsorbents mixed with micropores and mesopores and solids containing narrow crack pores. This confirms that the 13X zeolite added to GEO-6 forms this type of hysteresis loop by combining the micropores of the zeolite with the pores of the geopolymer itself. GEO-6HC also belongs to the H4 type hysteresis loop, but its hysteresis loop begins to appear at a relative partial pressure of 0.1. This is because the hydrothermal conversion will lead to the formation of a large number of mesoporous pores in the sample, and the mesoporous pores will lead to the appearance of capillary condensation, and the desorption pressure is always less than the adsorption pressure when the same adsorption amount occurs. The hysteresis loop of GEO-0 belongs to the H3 type hysteresis loop.
[0082] When the relative pressure is high, no saturated adsorption platform appears for GEO-0, GEO-6 and GEO-6HC. Similar to the type II isotherm adsorption curve, as the relative pressure increases, multi-layer adsorption of carbon-fixing materials is gradually formed. When the saturated vapor pressure is reached, the adsorption layers are infinite, resulting in no saturated adsorption platform.
[0083] 3) If Figure 4 As shown in the figure, by comparing the pore size distribution diagrams of GEO-0, GEO-6 and GEO-6HC, it can be seen that the pore volume of the mesopores is GEO-0<GEO-6<GEO-6HC. This is because the hydrothermal conversion causes the gel material in the geopolymer sample to transform into the zeolite phase, increasing the mesopores in the sample, which will enhance its adsorption capacity for carbon dioxide.
[0084] 4) Field emission electron microscopy scanning Figure 5 As shown:
[0085] The difference between GEO-6 and GEO-0 with or without the addition of 13X zeolite can be clearly seen in the picture. The added 13X zeolite (marked by the yellow circle in the picture) has a particle size of 2-5 μm, which is consistent with the size of the added zeolite 13X zeolite. At the same time, the marked zeolite particles in Figure (d) are scanned. It can be found that the hydrothermal product mainly contains 24.54wt% Si element, 14.4wt% Al element and 7.44wt% Na element. After calculation, n(Na):n(Al):n(Si)=1:3.29:1.94 is obtained, which is very close to the theoretical molecular structure formula of 13X zeolite n(Na):n(Al):n(Si)=1:3.35:2.02. Its composition is almost the same as that of 13X zeolite, which can prove that 13X zeolite does not participate in the polymerization process of geopolymer.
[0086] 5) Fourier infrared spectroscopy test such as Figure 6 As shown:
[0087] The FTIR spectra of each sample are shown in Figure 6 , all samples were at 3450 cm -1 A broad absorption peak can be observed at 1645 cm -1 The bending vibration of the -OH group of the free water molecule at 456 cm -1 The peak at is the bending vibration peak of the Si-O-Si bond.
[0088] Fly ash at 1100 cm -1 The strong absorption peak at 1020 cm-1 represents the asymmetric stretching vibration of Si-O-Si bonds, while the strong absorption peak at 1020 cm-1 of GEO-0 -1 There is a broad absorption peak at , which represents the asymmetric stretching vibration of Si-OT (T = Si or Al) bond in geopolymer sample. This bond is the characteristic chemical bond of successful geopolymer polymerization, which reflects the process of Al replacing Si in fly ash: the active substances in fly ash react under the action of alkaline activator, and alumina decomposes and releases Al 3+ During the geopolymer polymerization process, Al 3+ Replacement of Si 4+ The formation of long silicon-aluminum chains with Si-OT bonds is reflected in the fly ash at 1100 cm-1 in FTIR. -1 The strong absorption peak at 1020 cm-1 was shifted to 1020 cm-2. -1 Nearby, it is confirmed that some Si-O-Si bonds are converted into Si-O-Al bonds. However, since the mass fractions of aluminum oxide and silicon dioxide in fly ash are not equal, Al 3+ Cannot completely replace Si 4+ , at 870 cm -1 There is an inconspicuous symmetrical stretching vibration peak of Si-O-Si bond at the center, which represents the unreacted fly ash particles in the system.
[0089] 13X zeolite at 990 cm -1 The strong broad peak at 755 cm is due to the asymmetric stretching vibration of Si-OT (T = Si or Al) inside 13X zeolite, which increases the vibration amplitude of the absorption peak at this location; -1 The absorption peak at 562 cm is due to the symmetric stretching vibration of the tetrahedral Si-O-Si bond and Al-O-Al bond inside 13X zeolite. -1 The peak at 13X is the double six-membered ring vibration absorption peak of 13X zeolite, which is the characteristic absorption peak of 13X zeolite.
[0090] Compared with GEO-0, GEO-6 added 13X zeolite, resulting in a -1 The peak at 990 cm -1 This is because there are more Si-OT bonds in 13X zeolite, and the asymmetric stretching vibration of the internal Si-OT (T = Si or Al) increases the vibration amplitude of the absorption peak at 755 cm -1 The absorption peaks are caused by the symmetric stretching vibrations of the tetrahedral Si-O-Si bonds and Al-O-Al bonds in the added 13X zeolite. -1 The absorption peak at the center is the double six-membered ring vibration absorption peak of 13X zeolite, which is the characteristic absorption peak of 13X zeolite. This also proves that 13X zeolite and geopolymer are uniformly mixed and coexist.
[0091] GEO-6HC at 755 cm -1 and 562 cm -1 The vibration absorption peak at is broader than that at GEO-6, proving that more Si-OT bonds are formed during the hydrothermal transformation.
[0092] In the FTIR spectrum, the formation of chemical bonds such as Si-OT illustrates the extent to which geopolymerization generates amorphous gel material. Although it is difficult to judge the extent of geopolymer polymerization based solely on the position of each chemical bond in FTIR, it is of great significance for the qualitative analysis of geopolymerization reactions.
[0093] 6) Carbon dioxide isothermal adsorption test:
[0094] The samples GEO-0, GEO-6 and GEO-6HC were subjected to CO2 isothermal adsorption tests using an isothermal adsorption instrument. The tests were conducted at 40 °C and the pressure range was set to 0-5 MPa. The test results are shown in Figure 7 , Figure 8 , Fig. 9 .
[0095] At 40 °C and 5 MPa, the CO2 adsorption capacity of GEO-0 was 2.5 cm 3 / g, and the adsorption capacity of GEO-6 was 36.7 cm 3 / g, as shown in Table 2. The adsorption amount increased significantly after adding 13X zeolite, which proves that adding 13X zeolite is effective in improving the micropores of the sample. In the isothermal adsorption image of sample GEO-6, the adsorption amount of the sample increased very rapidly when the pressure was low, indicating that this part was due to the adsorption effect of the added microporous material, because micropores are easier to adsorb CO2 when the pressure is low, proving that the added microporous material 13X zeolite performs excellently.
[0096] At 40 °C and 5 MPa, the adsorption capacity of GEO-6HC was 70.6 cm 3 / g, and the adsorption capacity of GEO-6 was only 36.7 cm 3 / g. After the pore structure was improved by hydrothermal conversion, the adsorption capacity of the sample was significantly improved, which proves that hydrothermal conversion is effective in improving the pores of the sample. The mesopore specific surface area and micropore specific surface area determined by nitrogen adsorption and carbon dioxide adsorption tests show that the hydrothermal conversion group GEO-6HC increased the mesopore and micropore volume and specific surface area of the existing geopolymer GEO-6, as shown in Table 2. Compared with the isothermal adsorption image of GEO-6, when the pressure is low, the adsorption capacity of this part of the sample GEO-6HC is larger than that of GEO-6, which proves that hydrothermal conversion has excellent improvement on the performance of geopolymer in adsorbing CO2. In this case, 13X zeolite was used to optimize the micropores of the geopolymer and conduct CO2 adsorption tests. Under the temperature and pressure environment of 40 ℃ and 5 MPa, the CO2 adsorption capacity was 36.7 cm 3 / g; In this case, the product treated with 13X zeolite and hydrothermal conversion innovative technology comprehensively improved the micropores and mesopores that affect the CO2 adsorption performance of geopolymers, and the adsorption capacity reached 70.6 cm under the same working conditions. 3 / g.
[0097] Table 2 Comparison table of micropore and mesopore structure parameters and carbon dioxide adsorption capacity
[0098]
[0099] In summary, the fly ash-based modified geopolymer carbon-fixing material prepared by the present invention can not only introduce microporous materials to increase micropores, but also make the geopolymer amorphous three-dimensional gel undergo phase change to zeolite crystals to increase micropores and mesopores, and comprehensively regulate and improve the micropores and mesopores porosity that control the specific surface area of the material, thereby enhancing the adsorption capacity of carbon dioxide. This method not only improves the high added value utilization of fly ash, but also provides a new environmentally friendly solution for carbon capture and storage, which has significant social and economic significance. This case has opened up a new way to coordinate the disposal of carbon waste and realize the reuse of abandoned underground space.
[0100] The above description of the disclosed embodiments enables one skilled in the art to make or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the material amounts defined herein may be adjusted accordingly in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest range consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a fly ash-based polymer carbon fixation adsorption material, characterized in that: The method specifically comprises the following steps: S1: Weigh the raw materials respectively according to the proportion, then dissolve sodium hydroxide in water, heat in a water bath and add sodium silicate one by one, stir and dissolve to prepare an alkaline activator solution; S2: slowly adding fly ash to the alkaline activator solution prepared in S1, stirring to obtain a geopolymer slurry; S3: gradually adding 13X zeolite to the geopolymer slurry prepared in S2, stirring to obtain fly ash-13X zeolite composite geopolymer slurry; the 13X zeolite is a white powder with a particle size of 2 μm to 4 μm and a bulk density of ≥0.33 g / mL; S4: pouring the fly ash-13X zeolite composite geopolymer slurry prepared in S3 into a mold, and demoulding after constant temperature curing; S5: adding sodium hydroxide solution to the geopolymer sample after demoulding in S4, hydrothermal reaction, followed by washing and drying, to obtain the fly ash-based geopolymer carbon fixation adsorption material.
2. The method for preparing the fly ash-based polymer carbon fixation adsorption material according to claim 1, characterized in that: The raw materials are mainly composed of the following substances in parts by weight: 100 parts of fly ash, 55-70 parts of water, 10-34 parts of 13X zeolite, and 15-38 parts of alkali activator.
3. The method for preparing the fly ash-based polymer carbon fixation adsorption material according to claim 2, characterized in that: The alkaline activator is a mixed powder of sodium hydroxide and sodium silicate, and the alkaline activator includes 12 to 27 parts of sodium silicate and 3 to 11 parts of sodium hydroxide in parts by weight; Moreover, the modulus of the alkaline activator is 0.8-1.1; the sodium hydroxide is analytically pure powder; and the sodium silicate is analytically pure powder with a modulus of 2.
8.
4. The method for preparing the fly ash-based polymer carbon fixation adsorption material according to claim 1, characterized in that: The stirring speed in S2 is 400 r / min, and the stirring time is 4-6 min; the stirring speed in S3 is 400 r / min, and the stirring time is 1-2 min; the constant temperature curing temperature in S4 is 80°C, and the curing time is 24 h; the hydrothermal reaction temperature in S5 is 100°C, and the reaction time is 48 h.
5. The method for preparing the fly ash-based polymer carbon fixation adsorption material according to claim 1, characterized in that: The weight proportion of the sodium silicate in S1 added in batches is 1-2 parts, the weight proportion of the 13X zeolite in S3 added in batches is 3.4 parts, and the concentration of the sodium hydroxide solution in S5 is 2 mol / L, and the added amount is 54 parts.
6. A fly ash-based polymer carbon fixation adsorption material prepared by the method as claimed in claim 1.
7. The fly ash-based polymer carbon fixation adsorption material according to claim 6, characterized in that: The fly ash-based polymer carbon fixation adsorption material has a solid-liquid mass ratio of 0.55-0.7, a silicon-aluminum molar ratio of 1.7-2.0, and a constant curing temperature of 80°C.
Citation Information
Patent Citations
Method for preparing faujasite molecular sieve from flyash geopolymer
CN105152184A
In-situ loaded X-type zeolite porous geopolymer, preparation method and application
CN115090276A
Method for preparing 13X molecular sieve from fly ash solid phase
CN115385356A
Cited By
Slag geopolymer heavy metal adsorption material and preparation method thereof
CN120771831A
Lead-zinc tailing-based geopolymer thermal insulation material and preparation method thereof
CN122102586A